Health product advertising through news in lifestyle magazines - Erjavec, Karmen (Zdravstveno varstvo, 2011)
Background: In addition to doctors, the mass media are the key source of information about health issues. It is therefore very important what kind of messages they produce and convey. Some media researchers called attention to paid-for health-related texts, published as editorial content without being labelled as advertisements (now commonly referred to as advertorials). There is a lack of studies investigating the practice of such messages production. Methods: The aim of the study is to fill the gap in this research field by identifying characteristics of unlabelled health-related advertorials and thus give the readers the mechanisms they need to recognise them. Textual analysis of unlabelled health-related advertorials published by three Slovenian lifestyle magazines was combined with an ethnographic study. Results: Textual analysis indicated that readers can recognise advertorials by the partial and positive-only presentation of health-related products/services, which are described and promoted by using synonyms of effectiveness. Observation and in-depth interviews showed that the key actors in the production process are advertisers and newspaper marketing agents. Advertisers want to have control over texts presenting their products/ services. Marketing agents stress poor financial situation of their magazines. News producers claim that they carry out orders given by advertisers and marketing agents. Conclusion: By publishing unlabelled advertorials, lifestyle magazines privilege a pharmaceutical-commercial attitude to health. They promote the pharmaceutical industry by presenting it one-sidedly and in a simplified way, and by ascribing to it the capacity to solve health problems of people in a non-problematic way. A more complex social view of health issues, however, is neglected.
Keywords: advertising; novinarski prispevki; oglaševanje; promocija; Promotion; revije; zdravje